ANALYSIS OF ADVERSE DRUG REACTION RELATED HOSPITAL ADMISSIONS AND COMMON CHALLENGES ENCOUNTERED IN ADR REPORTING IN A TERTIARY CARE TEACHING HOSPITAL - JAMUNARANI.R; PRIYA.M (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The specific objective of this study is to see the clinical spectrum of Adverse Drug Reaction related hospital admissions in a tertiary care hospital and to identify common challenges encountered in ADR collection process. Methods: We did a cross sectional analytical study for a period of one year (Aug.2011-Sept.2012). After Institutional Ethical Committee approval, hospitalization due to adverse drug reactions from various departments in our tertiary care hospital was analyzed. Descriptive analysis of the ADR data collected is done by Microsoft Excel software and expressed as percentage comparison. Results: The number of hospital admissions due to ADR was 33. Of these 45.5percentwere male and 54.5percentwere female. Maximum number of patients (66.7percent) was reported with dermatological manifestations. Nearly 30.3percent of patients have taken these medicines as over the counter. Among the causative drugs, 57.5percent of ADR were due to Antibiotics, in which majority (42percent) is due to Quinolones, followed by NSAIDs (30.3percent), Antiepileptic (6.1percent), Antipsychotics (3.1percent) and hormonal drug (3.1percent). About two third of the patients (69.7percent) admitted with ADR were hospitalized for more than 5 days. According to the WHO Causality assessment scale, 12.1percent of the ADRs were certain, 75.8percent probable and 12.1percent were possible. Severity assessment by Modified Hartwig and Siegel scale revealed 66.7percent ADRs to be moderate, 27.3percent were severe and life threatening, 6.1percent were mild. Conclusion: A wide clinical spectrum of ADRs from maculopapular rash to serious SJS and TEN was observed in our study. Â For effective patient care, there is an urgent need to develop better preventive strategies and reporting of ADR by every health care provider to be made mandatory. Keywords: Adverse drug reactions, Pharmacovigilance, Patient Safety